Analysis of the Contributions of Essentialism and Existentialism Philosophy in the Implementation of Deep Learning in Science Learning - Muhammad Syahruddin Amin; Dina Fadilah; Salsabila Ayu Maulani; Malini Malini; Nesa Puspita Ariyani; Hulpa Irmayani; Solidia Wardani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The implementation of deep learning cannot be separated from philosophical assumptions that define the nature of knowledge and the role of teachers. However, studies on the contribution of philosophy—particularly essentialism and existentialism—to the implementation of deep learning are still limited. This literature study aims to analyze the interrelationship between deep learning and two contrasting educational philosophies—essentialism and existentialism— while simultaneously mapping out the points of compatibility between them. The result of the study shows that essentialism provides a structural foundation in the form of mastery of core knowledge and academic discipline, which are prerequisites for deep understanding, while existentialism contributes a reflective dimension in the form of freedom, authenticity, and the search for meaning, which strengthens the internalization of knowledge into life values. These two substantive strengths provide a philosophical foundation that reinforces the application of deep learning, through two interconnected stages: first, the structured mastery of core knowledge, followed by an authentic reflection and self-actualization. These findings are expected to contribute conceptually to the development of deep learning that balances structure and freedom of learning in primary school education